Fully-synthetic cutting fluid based on self-repairing material and preparation method of fully-synthetic cutting fluid
By using fully synthesized cutting fluid prepared by self-repair materials, the problems of degradation of lubrication performance and corrosion of cutting fluid under high load and high temperature conditions in the prior art are solved, high lubricity and corrosion resistance are achieved, and processing quality is improved.
Patent Information
- Application Number
- CN202510052430.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lubricating performance of existing fully synthetic cutting fluids under high load and high temperature conditions has deteriorated and corrosion problems may occur.
The fully synthetic cutting fluid is prepared by self-healing materials, and the self-healing microcapsules are prepared by polymer preproduct and chain expansion reaction, and mixed with other components to form a cutting fluid with excellent lubricating effect and corrosion resistance.
It achieves high lubricity and corrosion resistance under high load and high temperature conditions, extends the service life of cutting fluid, and improves processing quality.
Smart Images

Figure CN119463955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal cutting lubrication, and relates to a fully synthetic cutting fluid based on a self-repairing material and a preparation method thereof. Background Art
[0002] Fully synthetic cutting fluid refers to a type of cutting fluid that is based on synthetic oil (such as synthetic ester, polyether, etc.) and is formulated by adding various functional additives such as surfactants, extreme pressure additives, antioxidants, preservatives, etc. It does not contain mineral oil and animal and vegetable oils, and has high lubricity, cooling performance and environmental protection. Compared with other types of cutting fluids, the thermal conductivity of fully synthetic cutting fluids is usually higher than that of mineral oil cutting fluids, which effectively improves the heat dissipation capacity of the cutting area, reduces the heat accumulation during the processing, and reduces the thermal deformation of the workpiece and tool wear. At the same time, the synthetic ester and polyether components in the fully synthetic cutting fluid have good lubricity and can form an effective lubricating film during the cutting process to reduce friction. In some high-precision or high-speed cutting processes, fully synthetic cutting fluids can effectively reduce surface roughness and improve processing quality. Compared with mineral oil cutting fluids, synthetic cutting fluids are easier to degrade and usually do not contain harmful substances such as aromatic hydrocarbons and heavy metals. Its low toxicity and degradability make fully synthetic cutting fluids less polluting to the environment, which meets the needs of modern green manufacturing. The patent application with publication number CN107384561A discloses a fully synthetic cutting fluid; it is obtained by mixing and stirring a rust inhibitor, an extreme pressure agent, a surfactant, a corrosion inhibitor, a sedimentation agent, a lubricant, a bactericide, a defoaming agent and deionized water. In terms of corrosion protection, the corrosion inhibitor is directly added. In actual use, the corrosion protection effect will weaken with the increase of use time. Although fully synthetic cutting fluid has significant advantages in many aspects, there are still some problems in actual use. Under high load and high temperature conditions, the lubrication performance of the cutting fluid may decrease, and after long-term use, a certain degree of corrosion may occur. Therefore, we need to prepare a fully synthetic cutting fluid that can maintain high lubricity and high corrosion resistance. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention aims to provide a fully synthetic cutting fluid based on self-repairing materials and a preparation method thereof, firstly preparing a polymer pre-product, then obtaining self-repairing microcapsules through a chain extension reaction, and finally mixing the self-repairing microcapsules with other components to obtain a final fully synthetic cutting fluid. The cutting fluid has excellent lubrication effect and corrosion resistance, thus meeting the needs of actual production.
[0004] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, the preparation method comprising: Step S1, drying and dehydrating castor oil at a first temperature under vacuum, mixing the dried castor oil with isocyanate, continuously stirring at a second temperature at a first stirring speed, adding a catalyst, and continuing the reaction to obtain a pre-product; Step S2, adding the pre-product, diphenylmethane diisocyanate, and butyl acetate to the surfactant solution, stirring continuously at a second stirring speed under an ice water bath, then adjusting the stirring speed to a third stirring speed, adding a chain extender, reacting at a third temperature, and drying to obtain self-healing microcapsules; Step S3, mixing the synthetic ester and polyether evenly, and then sequentially adding nonionic surfactant, antioxidant, preservative, phosphate ester, stearic acid, self-repairing microcapsule, water and monoacid and mixing evenly to obtain a fully synthetic cutting fluid based on self-repairing material.
[0005] The shell of the self-healing capsule is polyurea. First of all, in terms of reducing friction, the molecular structure of polyurea is composed of chain segments connected by urea groups. These chain segments have a certain flexibility and can form a relatively soft lubricating layer between the friction surfaces. During the friction process, the polyurea molecules can slide along the contact surface to reduce direct contact with the metal, thereby reducing friction. This flexible structure enables polyurea to adapt to different contact forms and load changes, ensuring the stability of the friction coefficient; at the same time, the urea group can interact with other molecules or material surfaces through hydrogen bonds, van der Waals forces, etc. Since the nitrogen atoms and hydrogen atoms in the urea group have strong polarity, the polyurea molecules can better adhere to the surface during friction. The surface of the metal is adsorbed to form an adsorption layer, which reduces the direct contact of the metal surface and effectively reduces the friction coefficient. Polyurea materials usually have a lower surface energy, which enables them to form a certain lubricating layer, reduce the direct contact area of the contact surface and thus reduce friction. It is easier to form a lubricating film under high load conditions, reduce physical wear and enhance the lubrication effect. Another key feature of polyurea is its self-repairing ability. During the friction process, the friction surface is often damaged to a certain extent. The polyurea microcapsules can break during the friction process and release repair components that can quickly fill the cracks and wear areas and restore the integrity of the lubricating film. Even if the friction surface is damaged, polyurea can maintain the stability of the lubricating film through its repair effect.
[0006] In terms of corrosion resistance of self-healing capsules, the nitrogen atom in the urea group carries a lone pair of electrons, while the double bond formed by the carbon atom and the oxygen atom has a strong polarity, which enables polyurea to form a stable interaction with the oxide layer or polar groups on the metal surface, enhancing the adhesion of polyurea. This polarity gives polyurea a strong adsorption capacity, which helps polyurea to combine with the metal surface to form a strong protective film. Due to the chemical stability of the urea-based structure, polyurea has strong acid and alkali resistance and will not undergo obvious degradation or reaction in acidic or alkaline environments. Therefore, it can effectively prevent corrosion of metal surfaces under these conditions; hydrolysis is an important factor in the metal corrosion process, especially in aqueous environments. The molecular structure of polyurea has excellent resistance to hydrolysis. Polyurea can form a dense waterproof layer on the metal surface, which can effectively isolate external moisture and reduce direct contact of moisture with the metal surface. In this way, polyurea enhances the metal's resistance to water corrosion; in saline environments, polyurea also exhibits good corrosion resistance. Due to the interaction between the polar groups in the polyurea molecules and the metal surface, it can maintain a stable adsorption layer in the salt solution, preventing salt from entering the metal surface through the pores, thereby reducing the corrosion rate of the metal.
[0007] In terms of thermal stability of self-healing capsules, the molecular structure of polyurea contains urea groups and isocyanate groups. These structural units give polyurea thermal stability, and its degradation temperature is relatively high (usually above 250°C). The urea groups in the polyurea molecules have strong hydrogen bond formation ability, which not only increases the interaction force between polyurea molecules, but also enables polyurea to maintain the stability of the molecular chain at high temperatures, making it difficult for polyurea molecules to break or degrade when heated; polyurea may undergo cross-linking reactions during the synthesis process to form a three-dimensional network structure. This cross-linking structure can enhance the thermal stability of polyurea, making it difficult for it to be thermally degraded or break its molecular chain under high temperature conditions. The cross-linking structure forms a stronger covalent bond or hydrogen bond network, allowing polyurea to maintain its physical form and chemical stability at high temperatures; the nitrogen atoms in the urea groups have a strong electron pair density and can exchange electrons with the oxygen atoms in the oxide to inhibit the occurrence of oxidation reactions, so polyurea can better maintain its stability in oxygen or oxidizing environments.
[0008] As a preferred technical solution of the present invention, in step S1, the first temperature is 100-120°C.
[0009] In some optional examples, the castor oil is dried and dehydrated for 3-5 hours.
[0010] In some optional examples, the isocyanate is isophorone diisocyanate, and the mass ratio of the castor oil to isophorone diisocyanate after drying is (45-55): (60-70).
[0011] In some optional examples, the second temperature is 85-95°C.
[0012] In some optional examples, the first stirring speed is 300-400 rpm.
[0013] In some optional examples, the catalyst is dibutyltin dilaurate, and the mass ratio of the dried castor oil to dibutyltin dilaurate is (45-55): (0.3-0.5).
[0014] In some optional examples, the reaction time after adding the catalyst is 3-5 hours.
[0015] As a preferred technical solution of the present invention, in step S2, the mass ratio of the pre-product to the diphenylmethane diisocyanate is (30-40): (15-20).
[0016] In some optional examples, the mass ratio of the diphenylmethane diisocyanate to the butyl acetate is (15-20): (5-8).
[0017] In some optional examples, the surfactant is sodium dodecylbenzene sulfonate; The mass ratio of the butyl acetate to the surfactant solution is (5-8): (150-200), and the mass fraction of the surfactant solution is 3-5wt.%.
[0018] In some optional examples, the second stirring speed is 1000-1500 rpm.
[0019] In some optional examples, the stirring time of the second stirring speed is 10-15 min.
[0020] In some optional examples, the third stirring speed is 200-300 rpm.
[0021] In some optional examples, the chain extender is an ethylenediamine solution, the mass ratio of butyl acetate to the ethylenediamine solution is (5-8): (3-5), and the mass fraction of the ethylenediamine solution is 5-10 wt.%.
[0022] In some optional examples, the third temperature is 50-60°C.
[0023] In some optional examples, the reaction time at the third temperature is 3-5h.
[0024] As a preferred technical solution of the present invention, in step S3, the synthetic ester is ethyl lactate; The polyether is polyethylene ether; The nonionic surfactant is polyether-modified polysiloxane, and the mass ratio of the ethyl lactate, the polyethylene ether and the polyether-modified polysiloxane is (60-70): (40-50): (1-2).
[0025] In some optional examples, the antioxidant is 2,6-di-tert-butyl-p-cresol; The preservative is benzisothiazolinone; The phosphate ester is octyl phosphate; The mass ratio of the 2,6-di-tert-butyl-p-cresol, benzisothiazolinone and phosphate is (0.5-1): (0.6-1.5): (5-10).
[0026] In some optional examples, the mass ratio of stearic acid, self-healing microcapsules and water is (2-4): (10-20): (80-100); The monoacid is one of neodecanoic acid, isooctanoic acid and isononanoic acid, and the mass ratio of stearic acid to the monoacid is (2-4): (5-10).
[0027] In a second aspect, the present invention provides a fully synthetic cutting fluid based on a self-repairing material prepared using the method for preparing a fully synthetic cutting fluid based on a self-repairing material described in the first aspect.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) The compactness of the polyurea shell helps to isolate the active ingredients in the cutting fluid from corrosive substances, especially in high temperature and high pressure cutting environments. It has a positive effect on preventing the penetration of corrosive media and isolating oxygen, thereby enhancing the material's corrosion resistance; (2) Polyurea has good thermal stability, which makes the cutting fluid difficult to decompose or volatilize during high temperature cutting, ensuring long-term stable operation, which is especially important for cutting processing applications with long-term high temperature operations, and helps the cutting fluid maintain consistent performance under harsh conditions; (3) The shell and contents of the microcapsule provide a long-lasting lubricating effect on the cutting surface by reducing the friction coefficient, which helps to reduce frictional heat generation. This lubricity helps to improve the stability of the cutting process and reduce tool wear. At the same time, the enhanced lubricity reduces the heat accumulation caused by friction, thereby helping to maintain the stability of the cutting fluid and reduce the degree of degradation of the cutting fluid in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A flow chart of a method for preparing a fully synthetic cutting fluid based on a self-repairing material provided in Examples 1 to 8 of the present invention; Figure 2 This is a SEM image of the self-repairing microcapsules prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0031] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their specifications and manufacturer information are as follows: Castor oil, purity ≥98%, Fucheng County Huanyu Oil Co., Ltd.; Isophorone diisocyanate, purity ≥99%, Tesco Chemical (Hubei) Co., Ltd.; Dibutyltin dilaurate, purity ≥99%, Nantong Haotai Chemical Products Co., Ltd.; Diphenylmethane diisocyanate, purity ≥99%, Jiangsu Bosite Chemical Technology Co., Ltd.; Butyl acetate, purity ≥99%, Yangtze River Acetyl Chemical Co., Ltd.; Sodium dodecylbenzene sulfonate, purity ≥99%, Nanjing Milan Chemical Co., Ltd.; Ethylenediamine, purity ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.; Ethyl lactate, purity ≥99%, Yancheng Hongtai Bioengineering Co., Ltd.; Polyvinyl ether, purity ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.; 2,6-di-tert-butyl-p-cresol, purity ≥99%, Zhejiang Zancheng Biotechnology Co., Ltd.; Benzisothiazolinone, purity ≥99%, Shouguang Xintai Fine Chemical Co., Ltd.; Phosphate, purity ≥99%, Guangdong Shengke Biochemical Technology Co., Ltd.; Stearic acid, purity ≥99%, Jiangsu Rayen Environmental Protection Technology Co., Ltd.; Neohexanoic acid, purity ≥99%, Xingtianwai Chemical (Shanghai) Co., Ltd.; 2-Ethylhexanoic acid, purity ≥99%, Shenyang Zhangming Chemical Co., Ltd.; Isononanoic acid, purity ≥99%, Jiangxi Jinyuantai Chemical Co., Ltd.; Other raw materials can be purchased from the market.
[0032] Example 1 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 105° C. for 3.2 h under vacuum, mixing 47 g of the dried castor oil with 63 g of isophorone diisocyanate, stirring continuously at 88° C. at 320 rpm, adding 0.34 g of dibutyltin dilaurate, and continuing the reaction for 3.3 h to obtain a pre-product; Step S2, adding 32g of the pre-product, 16.3g of diphenylmethane diisocyanate, and 5.7g of butyl acetate to 160g of a 3.8wt.% sodium dodecylbenzene sulfonate solution, stirring continuously at 1100rpm for 12min in an ice water bath, then adjusting the stirring speed to 220rpm, adding 3.6g of a 5.8wt.% ethylenediamine solution, reacting at 52°C for 3.4h, and obtaining self-healing microcapsules after drying; Step S3, mix 63g of ethyl lactate and 41g of polyethylene ether evenly, then add 1.2g of polyether modified polysiloxane, 0.61g of 2,6-di-tert-butyl-p-cresol, 0.69g of benzisothiazolinone, 5.5g of octyl phosphate, 2.5g of stearic acid, 12g of self-repairing microcapsules, 88g of water and 6.7g of neodecanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-repairing materials.
[0033] Figure 2 This is the SEM image of the self-healing microcapsules prepared in this example. The capsule shell is circular or slightly elliptical in shape, with neat edges and no obvious cracks observed, indicating that the capsule surface has good integrity and uniformity.
[0034] Example 2 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 100° C. for 3 h under vacuum, mixing 45 g of the dried castor oil with 60 g of isophorone diisocyanate, stirring continuously at 85° C. at 300 rpm, adding 0.3 g of dibutyltin dilaurate, and continuing the reaction for 3 h to obtain a pre-product; Step S2, adding 30g of the pre-product, 15g of diphenylmethane diisocyanate, and 5g of butyl acetate to 150g of a 3.0wt.% sodium dodecylbenzene sulfonate solution, stirring continuously at 1000rpm for 10min under an ice water bath, then adjusting the stirring speed to 200rpm, adding 3.0g of a 5.0wt.% ethylenediamine solution, reacting at 60°C for 5.0h, and obtaining self-healing microcapsules after drying; Step S3, mix 70g of ethyl lactate and 40g of polyethylene ether evenly, then add 2.0g of polyether modified polysiloxane, 0.50g of 2,6-di-tert-butyl-p-cresol, 1.5g of benzisothiazolinone, 10.0g of octyl phosphate, 2.0g of stearic acid, 10g of self-repairing microcapsules, 80g of water and 10g of neodecanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-repairing materials.
[0035] Example 3 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 103° C. for 3.7 h under vacuum, mixing 51 g of the dried castor oil with 62 g of isophorone diisocyanate, stirring continuously at 87° C. at a speed of 330 rpm, adding 0.37 g of dibutyltin dilaurate, and continuing the reaction to obtain a pre-product; Step S2, adding 34g of the pre-product, 16.3g of diphenylmethane diisocyanate, and 5.2g of butyl acetate to 157g of a 3.9wt.% sodium dodecylbenzene sulfonate solution, stirring continuously at 1300rpm for 14min in an ice water bath, then adjusting the stirring speed to 260rpm, adding 3.5g of a 6.6wt.% ethylenediamine solution, reacting at 56°C for 4.1h, and obtaining self-healing microcapsules after drying; Step S3, mix 65g of ethyl lactate and 43g of polyethylene ether evenly, then add 1.3g of polyether modified polysiloxane, 0.84g of 2,6-di-tert-butyl-p-cresol, 0.73g of benzisothiazolinone, 6.7g of octyl phosphate, 2.3g of stearic acid, 13g of self-repairing microcapsules, 89g of water and 6.4g of isooctanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-repairing materials.
[0036] Example 4 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 112° C. for 3.5 h under vacuum, mixing 48 g of the dried castor oil with 67 g of isophorone diisocyanate, stirring continuously at 88° C. at a speed of 350 rpm, adding 0.41 g of dibutyltin dilaurate, and continuing the reaction to obtain a pre-product; Step S2, adding 36g of the pre-product, 17.5g of diphenylmethane diisocyanate, and 6.3g of butyl acetate to 165g of a 4.2wt.% sodium dodecylbenzene sulfonate solution, stirring continuously at 1000rpm for 15min under an ice-water bath, then adjusting the stirring speed to 280rpm, adding 4.3g of a 6.9wt.% ethylenediamine solution, reacting at 57°C for 4.4h, and obtaining self-healing microcapsules after drying; Step S3, mix 60g of ethyl lactate and 41g of polyethylene ether evenly, then add 1.1g of polyether modified polysiloxane, 0.75g of 2,6-di-tert-butyl-p-cresol, 0.87g of benzisothiazolinone, 7.4g of octyl phosphate, 3.1g of stearic acid, 16g of self-healing microcapsules, 91g of water and 6.7g of isononanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-healing materials.
[0037] Example 5 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 110° C. for 4.2 h under vacuum, mixing 51 g of the dried castor oil with 62 g of isophorone diisocyanate, stirring continuously at 86° C. at a speed of 340 rpm, adding 0.43 g of dibutyltin dilaurate, and continuing the reaction to obtain a pre-product; Step S2, adding 39g of the pre-product, 17.8g of diphenylmethane diisocyanate, and 6.6g of butyl acetate to 162g of a 4.0wt.% sodium dodecylbenzene sulfonate solution, stirring continuously at 1100rpm for 12min in an ice water bath, then adjusting the stirring speed to 240rpm, adding 4.0g of a 7.2wt.% ethylenediamine solution, reacting at 53°C for 4.1h, and obtaining self-healing microcapsules after drying; Step S3, mix 63g of ethyl lactate and 45g of polyethylene ether evenly, then add 1.7g of polyether modified polysiloxane, 0.86g of 2,6-di-tert-butyl-p-cresol, 1.2g of benzisothiazolinone, 7.8g of octyl phosphate, 3.5g of stearic acid, 18g of self-repairing microcapsules, 95g of water and 7.3g of neodecanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-repairing materials.
[0038] Example 6 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 116° C. for 3.4 h under vacuum, mixing 50 g of the dried castor oil with 67 g of isophorone diisocyanate, stirring continuously at 88° C. at a speed of 310 rpm, adding 0.40 g of dibutyltin dilaurate, and continuing the reaction to obtain a pre-product; Step S2, adding 32g of the pre-product, 17.1g of diphenylmethane diisocyanate, and 7.2g of butyl acetate to 182g of a 4.3wt.% sodium dodecylbenzene sulfonate solution, stirring at 1300rpm for 14min in an ice water bath, then adjusting the stirring speed to 220rpm, adding 3.7g of a 7.7wt.% ethylenediamine solution, reacting at 56°C for 4.6h, and obtaining self-healing microcapsules after drying; Step S3, mix 67g of ethyl lactate and 41g of polyethylene ether evenly, then add 1.3g of polyether modified polysiloxane, 0.81g of 2,6-di-tert-butyl-p-cresol, 0.94g of benzisothiazolinone, 8.6g of octyl phosphate, 3.1g of stearic acid, 14g of self-repairing microcapsules, 92g of water and 7.8g of neodecanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-repairing materials.
[0039] Example 7 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 106° C. for 4.5 h under vacuum, mixing 51 g of the dried castor oil with 62 g of isophorone diisocyanate, stirring continuously at 86° C. at a speed of 360 rpm, adding 0.43 g of dibutyltin dilaurate, and continuing the reaction to obtain a pre-product; Step S2, adding 37g of the pre-product, 18.6g of diphenylmethane diisocyanate, and 7.9g of butyl acetate to 189g of a 4.8wt.% sodium dodecylbenzene sulfonate solution, stirring continuously at 1400rpm for 13min in an ice water bath, then adjusting the stirring speed to 260rpm, adding 4.6g of a 8.4wt.% ethylenediamine solution, reacting at 57°C for 4.2h, and obtaining self-healing microcapsules after drying; Step S3, mix 68g of ethyl lactate and 45g of polyethylene ether evenly, then add 1.6g of polyether modified polysiloxane, 0.83g of 2,6-di-tert-butyl-p-cresol, 1.28g of benzisothiazolinone, 7.5g of octyl phosphate, 3.3g of stearic acid, 16g of self-repairing microcapsules, 90g of water and 6.3g of isooctanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-repairing materials.
[0040] Example 8 This embodiment provides a method for preparing a fully synthetic cutting fluid based on a self-repairing material, such as Figure 1 As shown, the preparation method specifically comprises the following steps: Step S1, drying and dehydrating castor oil at 111° C. for 4.6 h under vacuum, mixing 50 g of the dried castor oil with 64 g of isophorone diisocyanate, stirring continuously at 94° C. at a speed of 340 rpm, adding 0.46 g of dibutyltin dilaurate, and continuing the reaction to obtain a pre-product; Step S2, adding 32g of the pre-product, 17.6g of diphenylmethane diisocyanate, and 6.7g of butyl acetate to 180g of a 4.1wt.% sodium dodecylbenzene sulfonate solution, stirring continuously at 1100rpm for 12min under an ice-water bath, then adjusting the stirring speed to 230rpm, adding 4.2g of a 6.2wt.% ethylenediamine solution, reacting at 52°C for 4.5h, and obtaining self-healing microcapsules after drying; Step S3, mix 63g of ethyl lactate and 42g of polyethylene ether evenly, then add 1.4g of polyether modified polysiloxane, 0.74g of 2,6-di-tert-butyl-p-cresol, 1.15g of benzisothiazolinone, 7.1g of octyl phosphate, 3.0g of stearic acid, 19g of self-repairing microcapsules, 93g of water and 9.1g of isooctanoic acid in sequence, and mix evenly to obtain a fully synthetic cutting fluid based on self-repairing materials.
[0041] Comparative Example 1 This comparative example provides a fully synthetic cutting fluid based on self-healing materials. The difference between it and Example 1 is that the mass of diphenylmethane diisocyanate is adjusted to 26.3g. Compared with Example 1, the mass of diphenylmethane diisocyanate in this comparative example is increased by 10g, and the other process parameters and operating conditions are exactly the same as those in Example 1.
[0042] Comparative Example 2 This comparative example provides a fully synthetic cutting fluid based on self-healing materials. The difference between it and Example 1 is that the mass of diphenylmethane diisocyanate is adjusted to 6.3g. Compared with Example 1, the mass of diphenylmethane diisocyanate in this comparative example is reduced by 10g, and the other process parameters and operating conditions are exactly the same as those in Example 1.
[0043] For the fully synthetic cutting fluid prepared in the present invention, the appearance of the stock solution is observed by visual inspection; the appearance of the diluted solution (5% aqueous solution) is observed based on GB / T 6144-2010 / 5.2; the corrosion test method is based on GB / T 6144-2010 / 5.6; the maximum no-seizure load PB value test method is based on GB / T 3142-2019; the test results are shown in Table 1.
[0044] Table 1 Test results of a fully synthetic cutting fluid based on self-repairing materials
[0045] From the data of Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the corrosion test result and the maximum no-seizure load PB value in Comparative Example 1 are lower than those in Example 1; the corrosion test result in Comparative Example 2 is lower than that in Example 1, and the maximum no-seizure load PB value is higher than that in Example 1. The corrosion test results of the fully synthetic cutting fluid prepared in Example 1 are all qualified and have good lubrication effect. This is because in Comparative Example 1, the content of diphenylmethane diisocyanate is too high. Although the high cross-linking density formed by the excessive diphenylmethane diisocyanate makes the polyurea network more compact and can effectively block the penetration of corrosive ions or molecules and slow down the corrosion process, the unreacted free -NCO group may cause the stability of the material to decrease, because the free -NCO group will further hydrolyze in an environment with high humidity, affecting the chemical stability of the material. At the same time, the higher cross-linking density will make the polyurea structure harder and reduce its fluidity, so the flexibility and lubrication performance of the material will decrease. In comparative example 2, when diphenylmethane diisocyanate is insufficient, the isocyanate groups are relatively few, which will lead to a looser polyurea chain structure, a lower crosslinking density, and a weaker intermolecular bonding force, making it easier for corrosive substances to penetrate into the material, resulting in a decrease in anti-corrosion performance. Especially in high humidity or high salt environments, the low density of the material makes its corrosion resistance insufficient; the lubricity and flexibility of polyurea will be improved at low crosslinking density, because the mobility of the molecular chain is increased, and a lubricating film can be better formed. The loosely structured polyurea surface is prone to form a certain slip effect under the action of friction, thereby improving lubricity.
[0046] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a fully synthetic cutting fluid based on self-repairing materials, characterized in that: The preparation method is: Step S1, drying and dehydrating castor oil at a first temperature under vacuum, mixing the dried castor oil with isocyanate, continuously stirring at a second temperature, adding a catalyst, and continuing the reaction to obtain a pre-product; Step S2, adding the pre-product, diphenylmethane diisocyanate and butyl acetate to the surfactant solution, stirring continuously in an ice water bath, adjusting the stirring speed, adding a chain extender, reacting at a third temperature, and drying to obtain self-repairing microcapsules; Step S3, mixing the synthetic ester and the polyether uniformly, and then sequentially adding a nonionic surfactant, an antioxidant, a preservative, a phosphate ester, stearic acid, a self-repairing microcapsule, water and a monoacid to obtain a fully synthetic cutting fluid based on a self-repairing material after mixing uniformly; The mass ratio of the pre-product to the diphenylmethane diisocyanate is (30-40): (15-20); The mass ratio of the diphenylmethane diisocyanate to the butyl acetate is (15-20): (5-8).
2. The method for preparing a fully synthetic cutting fluid based on self-repairing materials according to claim 1, characterized in that: In step S1: The first temperature is 100-120°C; The drying and dehydration time of the castor oil is 3-5h; The isocyanate is isophorone diisocyanate, and the mass ratio of the castor oil to isophorone diisocyanate after drying is (45-55): (60-70).
3. The method for preparing a fully synthetic cutting fluid based on self-repairing materials according to claim 1, characterized in that: In step S1: The second temperature is 85-95°C; The catalyst is dibutyltin dilaurate, and the mass ratio of castor oil to dibutyltin dilaurate after drying is (45-55): (0.3-0.5); The reaction time after adding the catalyst is 3-5h.
4. The method for preparing a fully synthetic cutting fluid based on self-repairing materials according to claim 1, characterized in that: In step S2: The surfactant is sodium dodecylbenzene sulfonate; The mass ratio of the butyl acetate to the surfactant solution is (5-8): (150-200), and the mass fraction of the surfactant solution is 3-5wt.%.
5. The method for preparing a fully synthetic cutting fluid based on self-repairing materials according to claim 1, characterized in that: In step S2: The chain extender is an ethylenediamine solution, the mass ratio of butyl acetate to the ethylenediamine solution is (5-8): (3-5), and the mass fraction of the ethylenediamine solution is 5-10wt.%; The third temperature is 50-60°C; The reaction time at the third temperature is 3-5h.
6. The method for preparing a fully synthetic cutting fluid based on self-repairing materials according to claim 1, characterized in that: In step S3: The synthetic ester is ethyl lactate; The polyether is polyethylene ether; The nonionic surfactant is polyether-modified polysiloxane, and the mass ratio of the ethyl lactate, the polyethylene ether and the polyether-modified polysiloxane is (60-70): (40-50): (1-2).
7. The method for preparing a fully synthetic cutting fluid based on self-repairing materials according to claim 1, characterized in that: In step S3: The antioxidant is 2,6-di-tert-butyl-p-cresol; The preservative is benzisothiazolinone; The mass ratio of the 2,6-di-tert-butyl-p-cresol, benzisothiazolinone and phosphate is (0.5-1): (0.6-1.5): (5-10).
8. The method for preparing a fully synthetic cutting fluid based on self-repairing materials according to claim 1, characterized in that: In step S3: The phosphate ester is octyl phosphate; The mass ratio of stearic acid, self-repairing microcapsules and water is (2-4): (10-20): (80-100); The monoacid is one of neodecanoic acid, isooctanoic acid and isononanoic acid, and the mass ratio of stearic acid to the monoacid is (2-4): (5-10).
9. A fully synthetic cutting fluid based on a self-repairing material prepared according to the method for preparing a fully synthetic cutting fluid based on a self-repairing material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Fully synthetic cutting fluid
CN107384561A
Special cutting fluid for stainless steel and preparation method thereof
CN118879388A